Dynamics of the incidence of acute and chronic inflammatory polyneuropathies in adults in the Leningrad region - E. A. Skornyakova; L. G. Zaslavskii (Нервно-мышечные болезни)
Background. Inflammatory polyneuropathies (IPNP) are diseases caused by an immune response against antigens in the peripheral nervous system. Epidemiological research is essential for health resource planning.Objective: to assess the clinical and epidemiological characteristics of acute and chronic IPNP in adults in the Leningrad region.Materials and methods. We analyzed the incidence of acute and chronic IPNP the Leningrad region for the last 24 years.Results. A gradual increase in the incidence rate since 2003 with slight fluctuations has been shown. A particularly significant increase was recorded in 2015 from 14 (2014) to 22 patients, while in previous years fluctuations ranged from 4 to 10 people. In 2016 and 2017, the number of cases increased even more to 26–27 per year (there are 1 600 000 residents over 18 years of age in the region). At the same time, an increase in the incidence of both Guillain–Barré syndrome (GBS) and chronic inflammatory demyelinating polyneuropathy (CIDP) was noted. The incidence of GBS in the last 10 years was 0.18–0.88, the incidence of CIDP was the same 0.18–1.0 per 100 000 population. With GBS, women were more likely to get sick, with CIDP – men. With GBS, the debut was more often in winter (35 %), in summer and autumn, 25 % each, less often in spring – 17 %. The average age of GBS development in our study was 50.3 years. CIDP also fell ill at all age periods from 19 to 84 years (average age 55.6 years). The most common GBS triggers were acute respiratory viral infections in 36 % and enterocolitis in 13 %. Respiratory disorders requiring mechanical ventilation were observed in 8 % of patients with GBS.Conclusions. The incidence of IPNP in adults, both acute and chronic in the Leningrad region, is growing with some fluctuations. This should be taken into account for health resource planning.